Direct chemisorption-assisted nanotransfer printing with wafer-scale uniformity and controllability - Zhao, Zhi-Jun (2022)
Nanotransfer printing techniques have attracted significant attention due to their outstanding simplicity, cost-effectiveness, and high throughput. However, conventional methods via a chemical medium hamper the efficient fabrication with large-area uniformity and rapid development of electronic and photonic devices. Herein, we report a direct chemisorption-assisted nanotransfer printing technique based on the nanoscale lower melting effect, which is an enabling technology for two- or three-dimensional nanostructures with feature sizes ranging from tens of nanometers up to a 6 in. wafer-scale. The method solves the major bottleneck (large-scale uniform metal catalysts with nanopatterns) encountered by metal-assisted chemical etching. It also achieves wafer-scale, uniform, and controllable nanostructures with extremely high aspect ratios. We further demonstrate excellent uniformity and high performance of the resultant devices by fabricating 100 photodetectors on a 6 in. Si wafer. Therefore, our method can create a viable route for next-generation, wafer-scale, uniformly ordered, and controllable nanofabrication, leading to significant advances in various applications, such as energy harvesting, quantum, electronic, and photonic devices.